A sistemática filogenética e o tree thinking na formação de professores: uma análise dos projetos pedagógicos dos cursos de licenciatura em ciências biológicas da UFSCar - Silva, Matheus da (Universidade Federal de São Carlos, 2026)
This dissertation investigates how the curricula of pre-service Biology teacher education programs (Licenciatura) at the Federal University of São Carlos (UFSCar), Brazil, articulate the curricular status of phylogenetic systematics and tree thinking in initial teacher education. The empirical materials consist of the Course Curricular Projects (Projetos Pedagógicos de Curso, PPCs), treated as curriculum documents that frame and organize curricular knowledge. This qualitative documentary study compares seven PPC versions from the Araras, São Carlos, and Sorocaba campuses, including Araras (2007), São Carlos (2015, 2025), Sorocaba full-time (2010, 2023), and Sorocaba evening (2008, 2022). The corpus was analyzed through Discursive Textual Analysis (DTA), articulating unitarization, categorization, and the production of an interpretive metatext, with the reading guided by four analytical categories: formative rationalities in teacher education, mechanisms of theory–practice integration, the curricular status of phylogeny, and epistemological and pedagogical coherence. The findings indicate that phylogeny appears with variable intensity as a recognized scientific language and content within the core disciplinary subjects, especially in syllabi and bibliographies, and that recent reforms, particularly in Sorocaba, institutionalize foundational systematics as mandatory components of the curriculum. At the same time, curricular prescription does not transform phylogenetic systematics, treated primarily as content, into phylogenetic literacy or into tree-thinking operations, since tree thinking remains absent from the intended graduate profile and expected competencies and is not articulated in longitudinal teaching-practice components or in the teaching practicum. In PPCs that explicitly state evolution as an integrating axis, there is likewise no indication of tree thinking as an organizing principle for biological content and biological reasoning. This dissertation argues that phylogeny as content and phylogenetic literacy as a teaching competence correspond to distinct regimes of curricular prescription. The former is sustained by disciplinary presence and distribution, whereas the latter depends on decisions regarding compulsory status, timing and sequencing, and curricular textual specification that make possible the acquisition of tree-thinking operations throughout the program. Finally, the study proposes directions for curricular redesign aimed at institutionalizing these operations as organizing principles for Biology teaching.
Phylogenetic systematics and tree thinking in pre-service teacher education: an analysis of the pedagogical projects of UFSCar’s biological sciences teacher education programs
Keywords: Cladística; Formação inicial de professores; Currículo; Filosofia da biologia; Ensino de biologia; Cladistics; Pre-service teacher education; Curriculum; Philosophy of biology; Biology education; CIENCIAS HUMANAS::EDUCACAO::CURRICULO; CIENCIAS HUMANAS::EDUCACAO::PLANEJAMENTO E AVALIACAO EDUCACIONAL::AVALIACAO DE SISTEMAS, INSTITUICOES, PLANOS E PROGRAMAS EDUCACIONAIS; CIENCIAS BIOLOGICAS; 4. Educação de Qualidade